Multi-Point Interaction of Partially Conductive Cracks with Sweep Frequency Eddy Currents in Electromagnetic Non-Destructive Evaluation - Milan Smetana; Daniela Gombarska; Ladislav Janousek; Filip Vaverka (Applied Sciences, 2022)
An investigation of real corrosion cracks that can be partially conductive in electromagnetic non-destructive evaluation using sweep-frequency eddy-current frequency-response analysis is carried out in this study. A new approach incorporating innovative solutions is proposed. The goal was to increase the probability of detection of real corrosion cracks in contrast to the conventional sweep-frequency method that is based on single-point signal detection. The proposed procedure was tested on real material specimens where differential responses were gained from real corrosion cracks. Seven austenitic steel plate specimens having corrosion cracks were inspected. Eddy-current responses due to the material cracks were sensed, while a multi-point approach was used for this purpose. The presented unique results clearly showed that the detection ability of a fixed probe driven with sweep-frequency excitation signal could be increased when the multi-point detection is used, and the gained signals are further mathematically processed.